2018
DOI: 10.1159/000492202
|View full text |Cite
|
Sign up to set email alerts
|

Polidocanol Foam Injected at High Doses with Intravenous Needle: The (Almost) Perfect Treatment of Symptomatic Internal Hemorrhoids

Abstract: Background and Aims: Hemorrhoid disorders are common. This study aimed to assess the efficacy and safety of polidocanol foam injected at high doses with intravenous needle for the treatment of symptomatic internal hemorrhoids that prolapse or bleed. Methods: We evaluated 2,000 consecutive patients with prolapsed hemorrhoids (grades II/III/IV) recruited over 6 years. Foam injection was performed in one to four sessions with polidocanol 2%: 10 mL of the mixture (2 mL liquid plus air) or 20 mL (4 mL liquid plus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
1
21
1
Order By: Relevance
“…Recently, Fernandes et al [27] evaluated 2.000 consecutive patients, with II-IV degree HD, treated with polidocanol 2%. The authors reported a 98% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fernandes et al [27] evaluated 2.000 consecutive patients, with II-IV degree HD, treated with polidocanol 2%. The authors reported a 98% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot agree with the authors. In fact, there are several studies in the literature, even if still very heterogeneous, which reported the results of polidocanol foam in the treatment of all stages of HD [ 4 6 ].…”
mentioning
confidence: 99%
“…Another case series that considered the use of foam for II–IV degree HD was published by Fernandes and colleagues in 2019 [ 6 ]. The authors enrolled 2000 consecutive patients reporting a 98% success rate.…”
mentioning
confidence: 99%
“…Complications of ESD treatment include bleeding, perforation, subcutaneous emphysema, and infection; thus, other feasible minimally invasive treatment methods should be actively attempted. In the treatment of GI hemangioma, Fernandes and Fonseca reported a clinical study on the treatment of internal hemorrhoids with a large dose of 2% polidocanol, which successfully reduced the rebleeding rate[ 5 ]. Igawa et al [ 6 ] reported a clinical case of a small intestinal hemangioma successfully treated with single-point injection of polidocanol, and the amount of polidocanol was calculated according to the surface area of the hemangioma.…”
Section: Discussionmentioning
confidence: 99%